Significance of nicotine and nicotinic acetylcholine receptors in Parkinson’s disease - Lin, Xia; Li, Qian; Pu, Min; Dong, Hao; Zhang, Qinghua (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease (PD) is a multifaceted neurodegenerative disorder characterized by the degeneration of dopaminergic neurons in the substantia nigra and the aggregation of α-synuclein. According to epidemiological data, PD is the second most prevalent neurodegenerative disorder after Alzheimer’s disease (AD) and has emerged as a significant global health concern. This review examines the intricate pathological mechanisms and high-risk factors associated with PD, and discusses the challenges in its clinical diagnosis and treatment. We elucidate the relationship between smoking and the reduced risk of PD, highlighting the potential neuroprotective effects of nicotine present in tobacco. The interaction between nicotine and nicotinic acetylcholine receptors (nAChRs) is analyzed in detail, emphasizing their neuroprotective capabilities and underlying molecular mechanisms. Furthermore, we analyze the structural and functional diversity of nAChRs and their roles in the pathological progression of PD. Our review aims to elucidate the complex interplay of genetic, environmental, and biochemical factors in PD and to propose future research directions that may facilitate therapeutic development.